Prevalence and factors associated with folic acid supplementation in pregnant women: systematic review and meta-analysis - Campos, Hudson Manoel Nogueira (2022)
This systematic review, registered under number CDR42020176877, summarizes the prevalence and factors associated with folic acid supplementation before and during pregnancy. Articles were selected from the Science Direct, Scielo.org and PubMed databases. Of the 30 articles selected for the systematic review, 25 were included in the meta-analysis. For folic acid use before pregnancy, the analysis showed: 25-29 years old (OR: 2.625; 95%CI:2,418-2,849); ? 30 years (OR: 3,367; 95%CI:3,079-3683), ? 35 years (OR: 1,250; 95%CI: 1,137-1,374); married (OR: 3.49; 95%CI: 2,71-4,495); ? 15 years of schooling (OR: 1.930; 95%CI:1,547-2,408), secondary education (OR: 2.449; 95%CI:2,275-2,635); ? tertiary education (OR: 3.203; 95%CI:2,941-3,488); income (OR: 2,329; 95%CI:2,192-2,474); planning pregnancy (OR: 3.261; 95%CI: 2,931-3,630). For use during pregnancy: 25-29 years old (OR: 1.539; 95%CI: 1,341-1,767), ? 30 years (OR: 1.502; 95%CI: 1,325-1,702); married (OR: 2,095; 95%CI: 1,838-2,388); Black (OR: 0.635; 95%CI: 0,556-0,725); ? 9 years of schooling (OR: 2,237; 95%CI: 2,003-2,499), secondary education (OR: 3,525; 95%CI: 3,026-4,108); ? complete tertiary education (OR: 6.486; 95%CI: 5,349-7,865); income (OR: 2.514; 95%CI: 2,225-2,840); planned pregnancy (OR: 2.079; 95%CI: 1,846-2,341); to perform prenatal care (OR: 15.085; 95%CI: 12,639-18,003). In conclusion, a multidisciplinary approach seems to be promising to overcome the barriers and difficulties that prevent preparing a healthy pregnancy.